Data Lakehouse: Benefits in small and medium enterprises - Blaž Čuš; Darko Golec (Mednarodno Inovativno Poslovanje)
This article argues that the collection and processing of structured and unstructured data is necessary in small and medium-sized enterprises to advance in the business. The architecture, as it is known today, of a Data Warehouse is superseded by the larger Data Lakehouse. It is based on open data formats with direct access and has excellent support for machine learning and data science. To the enterprises that currently process only structured data, so they are technologically behind the competition, Data Lakehouse can help to solve big challenges based on Data Warehouses and Data Lakes, including data obsolescence, unmanageable data, and misplaced data. In the article it is presented how small and medium-sized enterprises are choosing to make a technological shift in the direction of Data Lakehouse, which helps them with strategic decisions and further steps in the enterprise for faster growth and development.